2016
DOI: 10.1002/met.1579
|View full text |Cite
|
Sign up to set email alerts
|

Skill of short- to medium-range monsoon rainfall forecasts from two global models over India for hydro-meteorological applications

Abstract: The South Asian region is dominated by summer monsoon rainfall which, in many years, is associated with severe floods leading to socio‐economic losses. In India, areas with high population are exposed to heavy rainfall events and their associated risks. Indian monsoon rainfall simulation and prediction at various spatial and temporal scales are challenging scientific tasks for the weather/climate modelling community. Skilful short‐ and medium‐range predictions of rainfall from global numerical models during mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, there is a considerable reduction in easterly bias (and rainfall wet bias) during the monsoon season of 2014 and 2015 (figure not shown). Some of these improvements in the forecast rainfall during recent years may be attributed to the increased horizontal resolution (∼17 km), a new dynamical core (ENDGame) and a revised physics package (GA6.1) (Prakash et al 2016;Rakhi et al 2016). The spatial distribution of average rainy day counts (>1 mm d −1 ) over Indian region (land points only) during the nine monsoon seasons of 2007-2015 is presented in figure 5.…”
Section: Mean Monsoon Rainfall During 2007-2015mentioning
confidence: 99%
“…However, there is a considerable reduction in easterly bias (and rainfall wet bias) during the monsoon season of 2014 and 2015 (figure not shown). Some of these improvements in the forecast rainfall during recent years may be attributed to the increased horizontal resolution (∼17 km), a new dynamical core (ENDGame) and a revised physics package (GA6.1) (Prakash et al 2016;Rakhi et al 2016). The spatial distribution of average rainy day counts (>1 mm d −1 ) over Indian region (land points only) during the nine monsoon seasons of 2007-2015 is presented in figure 5.…”
Section: Mean Monsoon Rainfall During 2007-2015mentioning
confidence: 99%
“…The aforementioned studies refer to longer climate simulations, but forecasting the Indian Summer Monsoon is also challenging at shorter timescales appropriate to numerical weather prediction (NWP) (Ranade et al 2014;Gadgil and Srinivasan 2012), and the MetUM also shows rainfall biases at NWP scales (Prakash et al 2016;Mitra et al 2013). Categorical yes/no forecasts of rainfall are generally good, but it is rather more difficult to produce good forecasts of rainfall amount (Joshi and Kar 2016;Kumar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Global Land (GL) version 6.1 defines the global land science configuration, which uses the Joint UK Land Environment Simulator (JULES) community land surface model (Best et al, 2011;Clark et al, 2011). Prakash et al (2016) showed good skill for five-day forecasts of the 2014 Indian monsoon season with this MetUM configuration. In order to provide more local detail in the forecasts for the campaign, a bespoke limited-area model (LAM) was developed covering a domain of 5…”
mentioning
confidence: 99%